227.5+h+4.9=0

Simple and best practice solution for 227.5+h+4.9=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 227.5+h+4.9=0 equation:


Simplifying
227.5 + h + 4.9 = 0

Reorder the terms:
227.5 + 4.9 + h = 0

Combine like terms: 227.5 + 4.9 = 232.4
232.4 + h = 0

Solving
232.4 + h = 0

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-232.4' to each side of the equation.
232.4 + -232.4 + h = 0 + -232.4

Combine like terms: 232.4 + -232.4 = 0.0
0.0 + h = 0 + -232.4
h = 0 + -232.4

Combine like terms: 0 + -232.4 = -232.4
h = -232.4

Simplifying
h = -232.4

See similar equations:

| 4/x=3/2 | | -8(v-5)=4-2v | | 2.9x+13.756=5-2.99x | | -9m^2-15m+6=-3m-10m^2 | | -5p-35=5(-6p+8) | | a=12+(11-1)7 | | 10x^10+100x^2+10x-10=0 | | 13x(-8)= | | 3x-4-10x-9= | | a=12+(4-1)7 | | 48.4=6c-2 | | 3(7-6x)=-87 | | n^2-10n+18=9 | | Y=-(x+2)(x-10) | | 7e-1=50.1 | | a=12+(2-1)7 | | 4x^2+1=a | | m^4-100=0 | | 3p^2-4p-2=-7 | | 3x=-2x+21 | | 6-8x=-3(2x+2) | | 2x(5+7)= | | 2ab-2ab-a-a+a+b+b-b= | | a=-3+(11-1)4 | | 6-3(5-2y)=17 | | a=-3+(5-1)4 | | 2x-(x-4)=5 | | S*4-35=73 | | -6y=-7y-1 | | a=-3+(3-1)4 | | -4x-7=-2x-3 | | 7(1-5m)-6=1-7m |

Equations solver categories